A Paleoecological model for northwest coast prehistory - Fladmark, Knut R. (University of Calgary, 1974)
Bibliography: p. 299-319. The evolution of the Northwest Coast cultural pattern is discussed in terms of changing energy availability through periods of environmental instability and quasi-stability. Evidence is presented for the simultaneous occurrenc e of two different archaeolo gica l traditions along the Northwest Coast between about 10,000 and 5,000 B.P. The first is characterized by a blade-andcore technology and de-emphasis of bifacial flaking. Site areas are associated with raised beaches and distributed along the whole coast north of central Queen Charlotte Sound . To the south, particularly on the lower Fraser and Columbia Rivers there occurs contemporaneously an entirely different tradition characterized by large leaf-shaped bifaces and a lack of a true blade-and-core technology. The distributional break between the two traditions corresponds precisely with the zero-isobar separating sea-level s significantly higher than present north of central Queen Charlotte Sound, and sea-levels significantly lower to the south. It is suggested that this correlation reflects the divergent effects of higher and lower sea-levels on the coastal environment and corresponding divergence of cultural adaptive strategies. The blade-and-core tradition probably represents a long-standing cultural adaptation to the inter-tidal and general marine resources of the sub-arctic Pacific region, with the southern tradition more heavily based on riverine and terrestrial resources. The rapid efflorescence of large semi-permanent settlements, art and wealth objects, and other features typical of ethnographic coastal cultures, 5,000 B.P. correlates with the stabilization of sea-level at about the present position along most of the coast at this time. It is suggested that gradient maturation of the river systems following coastline stabilization allowed the establishment of the massive and dependable salmon runs on which the dense and semi-sedentary populations of the ethnographic Northwest Coast were based.